2006
DOI: 10.1080/13803390500360372
|View full text |Cite
|
Sign up to set email alerts
|

Premorbid Intellectual Functioning and Risk of Schizophrenia and Spectrum Disorders

Abstract: Evidence from longitudinal studies indicates that lower IQ score in childhood and early adolescence increases risk of schizophrenia and schizophrenia spectrum disorders (SSD). This study investigated the association between premorbid IQ and risk of SSD in a population-based cohort of 17-year-old conscripts. Fifty four thousand males assessed by the Israeli Draft Board during two consecutive years were followed by means of the Israeli National Psychiatric Hospitalization Case Registry for up to 11 years. Tests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
66
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(70 citation statements)
references
References 57 publications
4
66
0
Order By: Relevance
“…Theoretically, the results further suggest higher intelligence to be protective against psychosis. An alternative model suggests that higher intelligence may act as a buffer against the effects of separate processes that modify (increase) the risk for psychosis (Khandaker et al, 2011) and therefore may act as protective factor (Reichenberg et al, 2006). Moreover, our results clearly indicate, as hypothesized, that markers for preexistent cognitive impairments are most prevalent among subjects diagnosed with psychoses.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Theoretically, the results further suggest higher intelligence to be protective against psychosis. An alternative model suggests that higher intelligence may act as a buffer against the effects of separate processes that modify (increase) the risk for psychosis (Khandaker et al, 2011) and therefore may act as protective factor (Reichenberg et al, 2006). Moreover, our results clearly indicate, as hypothesized, that markers for preexistent cognitive impairments are most prevalent among subjects diagnosed with psychoses.…”
Section: Discussionsupporting
confidence: 67%
“…Thus, while no differences were found in controls, lower PIQ than VIQ scores were assessed in "prepsychotic dropouts" up to large differences in current psychotic cases. In another but prospective conscript study, a general cognitive impairment was found to be predictive of later disorders from the schizophrenia spectrum, however, an additional risk was given by deficits in nonverbal reasoning (comparable to PIQ) (Reichenberg et al, 2006). This effect might be explained by neurodegenerative processes in specific areas of the brain during illness which involve fluid components of intelligence such as executive functions and working memory (Purcell et al, 1998;Amminger et al, 2000;Ojeda et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that atypical but not classical antipsychotics can reverse these cognitive deficits; however, in the clinic there is differing evidence for the efficacy of atypical antipsychotics in improving cognition with the CATIE study (Lieberman, 2006;Keefe et al, 2007) and the UK Cost Utility of the Latest Antipsychotic Drugs in Schizophrenia Study (CUtLASS; Jones et al, 2006; suggesting that antipsychotics actually have a limited effect. Cognitive dysfunction is a core characteristic of schizophrenia (Sullivan et al, 1994;Elvevag and Goldberg, 2000;Kuperberg and Heckers, 2000), occurring in 75-85% of patients (Reichenberg et al, 2006), and is becoming increasingly important as impaired cognition has been implicated in poor long-term functional outcome (Marder and Fenton, 2004) which can often persist when other symptoms may be improved with treatment (Gold et al, 1991;Heinrichs, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Despite strong evidence of poor premorbid intellectual functioning (for a meta-analytic review, see Aylward et al, 1984;Seidman et al, 2006;Reichenberg et al, 2006) and literature suggesting subtle functional impairments in years preceding clinical onset (e.g., , only a few studies have examined neurocognitive functioning among high-risk youth in relationship to vulnerability for conversion to Axis I psychosis.…”
Section: Introductionmentioning
confidence: 99%